2017
DOI: 10.1002/14651858.cd011572.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Placebo response and remission rates in randomised trials of induction and maintenance therapy for ulcerative colitis

Abstract: Placebo response and remission rates vary according to endoscopic disease severity and rectal bleeding score at trial entry, class of agent, disease duration, and the time point at which the primary outcome was measured. These observations have important implications for the design and conduct of future clinical trials in UC and will help researchers design trials, determine required sample sizes and also provide useful information about trial design features which should be considered when planning new trials. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 203 publications
2
14
0
Order By: Relevance
“…However, while psoriasis represents a sensitive disease model to detect potential differences in clinical efficacy and immunogenicity between adalimumab biosimilars and the RP, ongoing pivotal studies more frequently include patients with RA, perhaps reflecting both patient population size and the potential commercial impact of RA [30]. In ulcerative colitis (UC), high and variable placebo response rates [31,32] may also present a challenge for selection of this indication for biosimilar trials. The endpoints used in biosimilar clinical trials should be appropriate and sensitive enough to detect potential differences between the RP and the proposed biosimilar [19,20].…”
Section: Key Pointsmentioning
confidence: 99%
“…However, while psoriasis represents a sensitive disease model to detect potential differences in clinical efficacy and immunogenicity between adalimumab biosimilars and the RP, ongoing pivotal studies more frequently include patients with RA, perhaps reflecting both patient population size and the potential commercial impact of RA [30]. In ulcerative colitis (UC), high and variable placebo response rates [31,32] may also present a challenge for selection of this indication for biosimilar trials. The endpoints used in biosimilar clinical trials should be appropriate and sensitive enough to detect potential differences between the RP and the proposed biosimilar [19,20].…”
Section: Key Pointsmentioning
confidence: 99%
“…Improvement in outcomes following a placebo intervention has been well described in UC. A framework for evaluating this phenomenon includes consideration of: (1) neuro‐biologic factors, including true anti‐inflammatory effects from vagal nerve activity through the brain‐gut axis and spontaneous fluctuations in the natural history of the disease; and (2) trial design‐related factors, including potential inclusion of patients without confirmed inflammation at enrolment, regression to the mean and treatment response as measured by symptom‐based outcomes sensitive to patient expectancy . In this first meta‐analysis of placebo endoscopic and histologic rates in UC, we found that rates vary according to whether trials are designed for induction or maintenance, and for the endpoint of response and remission.…”
Section: Discussionmentioning
confidence: 98%
“…Historically, high placebo response rates in UC RCTs have reduced statistical efficiency and the heterogeneity in placebo response rates has made precise sample size calculations challenging . In a recent meta‐analysis of UC RCTs examining clinical endpoints based on the Mayo Clinic Score (MCS), the pooled estimates for clinical placebo response rates in induction and maintenance trials were 33% [95% confidence interval (CI) 29‐37%] and 22% [95% CI 17‐28%], respectively . The authors concluded that potential strategies for reducing clinical placebo response rates include mandating more rigorous trial inclusion criteria (including endoscopic disease thresholds), minimising study visits and adopting more stringent outcome definitions.…”
Section: Introductionmentioning
confidence: 99%
“…Complete search terms are reported in Data S1. The search terms were designed by an author with expertise in library sciences (CEP) and have been used in previous systematic reviews . Additionally, abstracts from Digestive Disease Week and United European Gastroenterology Week (2012‐2017), references from relevant studies, review articles, and meta‐analyses were also searched.…”
Section: Methodsmentioning
confidence: 99%
“…The search terms were designed by an author with expertise in library sciences (CEP) and have been used in previous systematic reviews. [13][14][15][16] Additionally, abstracts from…”
Section: Introductionmentioning
confidence: 99%